UPAYA PENINGKATAN KEWASPADAAN GUNA MENGHINDARI KECELAKAAN KERJA DI MV. SIAM - Fhadlan Ikhsan; Muhammad Syafril Sunusi; Agriani Pongkessu (STKIP Subang, 2026)
This study aims to identify the efforts that can be undertaken to prevent work accidents onboard merchant vessels, using MV. SIAM as a case study. A qualitative case-study approach was applied, with primary data collected through direct observation, in-depth interviews, and documentation during the author's sea practice (PRALA) from 8 April 2024 to 22 April 2025 in the Red Sea and Arabian Sea. Data were analysed descriptively through data reduction, data display, and conclusion drawing/verification. The findings show that the work accident experienced by a Boatswain, caused by a rebounding cutting disc while operating a portable grinder, resulted from a combination of individual negligence in pre-use equipment inspection, non-compliant use of personal protective equipment, unfit equipment condition, and weak on-site supervision. Continuous safety training, routine equipment inspection, strict enforcement of personal protective equipment use, and a transparent incident-reporting system are required to address these issues. Strengthening a consistent safety culture is expected to minimise the risk of work accidents and to sustain maritime safety onboard MV. SIAM.